2010
DOI: 10.1002/jtr.774
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between tourism receipts, real effective exchange rate and economic growth in Tunisia

Abstract: The objective of this paper is to analyse the role of tourism in the Tunisian economic growth. We used a trivariate model of real gross domestic product (GDP), real international tourism receipts and real effective exchange rate to discuss the relationship between tourism and economic growth. By using annual data for Tunisia for the period of 1970-2007, our results reveal that there is a cointegrating relationship between tourism and economic growth. In addition, our results for the Granger causality test indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
137
1
13

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(159 citation statements)
references
References 28 publications
8
137
1
13
Order By: Relevance
“…In the same equation, we have a unidirectional short-run causality running from output to the number of tourist arrivals, while bidirectional causality is supported in the long-run. These results are different from those provided by Belloumi [11] who argues that there is a long-run unidirectional relationship running from real international tourist receipts to GDP. This difference in results may be explained by the fact that we use the number of international tourist arrivals as a variable explaining tourism, while Belloumi [11] uses real international tourist receipts as a variable explaining tourism in Tunisia.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In the same equation, we have a unidirectional short-run causality running from output to the number of tourist arrivals, while bidirectional causality is supported in the long-run. These results are different from those provided by Belloumi [11] who argues that there is a long-run unidirectional relationship running from real international tourist receipts to GDP. This difference in results may be explained by the fact that we use the number of international tourist arrivals as a variable explaining tourism, while Belloumi [11] uses real international tourist receipts as a variable explaining tourism in Tunisia.…”
Section: Resultscontrasting
confidence: 99%
“…Allowing explicitly tourism to enter the production function as a deterministic variable of the output growth has been previously studied in a number of econometric surveys (Belloumi,[11]; Ben Jebli et al, [15]; Choyakh, [18]; Katircioglu, [27], [28]; Katircioglu et al, [29]). For the case of Tunisia, Belloumi [11] investigates the relationship between tourism receipts, the real effective exchange rate and economic growth over the period 1970-2007. The results provide supportive evidence for the presence a cointegrating relationship between economic growth and tourism.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite using research methodologies based on time series and/or panel data analytical techniques, empirical studies have shown mixed or even inconsistent results in terms of supporting the tourism-led economic growth hypothesis. Examples of studies that analyze the relationship between tourism and economic growth employing the Granger causality test with time series data analysis include Balaguer and Cantavella-Jorda [9], Durbarry [10], Gunduz and Hatemi-J [11], Brida, Carrera, and Risso [12], Chen and Chiou-Wei [13], Belloumi [16], Akinboade and Braimoh [17], Tang and Abosedra [18], and Tang and Tan [19]. These studies provide evidence in support of the tourism-led growth hypothesis.…”
mentioning
confidence: 99%
“…In supporting these views, Chang (2008), using heterogeneous panel cointegration, found unidirectional causality from tourism development to economic growth in Organisation for Economic Cooperation and development (OECD) countries whilst in non-OECD countries, found bidirectional causality between variables. On Bellaumi (2010) and Brida et al (2010) also found unidirectional causality from tourism to economic growth in Tunisia and Uruguay respectively. Furthermore, Tang (2011) and De MelloSampayo and de Sousa-Vale S (2011) also found unidirectional causality from tourism to economic growth in Malaysia and north European countries respectively.…”
Section: Review Of Literaturementioning
confidence: 85%